2021
DOI: 10.1111/ger.12563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of fluoride varnish in preventing caries amongst Long‐Term Care Facility Residents

Abstract: Objective: To evaluate the effectiveness of professionally applied fluoride varnish on the incidence of dental caries amongst older adults resident in LTCFs in Northern Ireland. Background:The oral health status of older adults within Long-Term Care Facilities (LTCFs) is significantly worse than their community living peers. Whilst evidence suggests an important role for fluoride varnish in preventing caries in this population, very few studies have evaluated this intervention. Materials and Methods: A quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Across all KQs, 16 studies (in 17 publications; total 3300 participants) were included (Figure 3). One randomized clinical trial (RCT) and 7 diagnostic accuracy studies addressed screening, and 4 RCTs and 5 nonrandomized trials addressed preventive interventions. The Table summarizes the evidence reviewed for this report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all KQs, 16 studies (in 17 publications; total 3300 participants) were included (Figure 3). One randomized clinical trial (RCT) and 7 diagnostic accuracy studies addressed screening, and 4 RCTs and 5 nonrandomized trials addressed preventive interventions. The Table summarizes the evidence reviewed for this report.…”
Section: Resultsmentioning
confidence: 99%
“…One fair-quality and 4 poor-quality trials evaluated topical fluorides (varnish or gels/solutions) vs placebo or no topical fluoride for prevention of dental caries in adults (eTables 5 and 6 in the Supplement). In all trials, topical fluorides were applied by dental professionals.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of an intervention with fluoride varnish and topical agents for reduction of RCLs depends on the interval and the frequency of application. For example, sodium fluoride varnish (Duraphat) is recommended to be applied four times per year [ 11 , 12 ]; however, a frequency of twice a year has also been shown to be effective in reducing the number of RCLs in care-dependent older adults [ 50 ]. Tan et al [ 55 ] performed an intervention using SDF only once a year; even at this relatively low rate of application, they were able to report greater effectiveness in reducing new RCLs incidence compared with the other substances (Duraphat or Cervitec) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,19 In addition, fluoride varnish was associated with decreased risk of developing new dental caries (relative risk, 0.25 [95% CI, 0.10-0.63]), translating to a number needed to treat of 3.1 (95% CI, 2.1-7.7). 1,19 A nonrandomized cluster trial 25 (n = 232) of older adults in long-term care facilities found no group differences in dental caries burden (based on DMFT/DFT [Decayed, Missing, and Filled Teeth/Decayed, Filled Teeth] score) at 1 year (adjusted mean difference, −0.04 [95% CI, −0.10 to 0.03]). 1,19 The 3 additional trials of other topical fluoride approaches (sodium fluoride 2% solution, stannous fluoride [30%] paste followed by aqueous solution, and acidulated phosphate fluoride [1.2%] at varied time frames) obtained inconsistent results.…”
Section: Effectiveness Of Preventive Interventionsmentioning
confidence: 99%